Pengaruh DAU, DAK, dan Belanja Modal terhadap Fiscal Stress pada Pemerintah Daerah Provinsi Sumatera Barat - Yurnal, Randy Givari; Handayani, Dian Fitria (Jurnal Eksplorasi Akuntansi, 2024)
The purpose of this study is to ascertain the impact of capital spending, the Special Allocation Fund (DAK), and the General Allocation Fund (DAU) on the budgetary pressures placed on the provincial regional administration of West Sumatra. Purposive sampling was the method of sampling that was applied. For the 2019–2021 timeframe, 19 districts/cities in the West Sumatra Province were included in the research sample. Secondary data from the Ministry of Finance's DJPK website and the Central Statistics Agency (BPS) were utilized. Multiple regression analysis, which includes the t, f, and coefficient of determination tests, is the analytical technique employed. The regression test's findings indicate that capital spending has no significant impact on fiscal stress, but DAK and DAU have substantial negative and positive effects, respectively. the concurrent impact of capital spending, DAU, and DAK on major fiscal strain in the West Sumatra Province regional government in 2019–2021.